Предмет: Математика,
автор: aldiyar5624
помогите пж
![\frac{x + 2}{9} - 1 = \frac{2x + 1}{18} - \frac{x}{6} \frac{x + 2}{9} - 1 = \frac{2x + 1}{18} - \frac{x}{6}](https://tex.z-dn.net/?f=++%5Cfrac%7Bx+%2B+2%7D%7B9%7D+++-+1+%3D++%5Cfrac%7B2x+%2B+1%7D%7B18%7D++-++%5Cfrac%7Bx%7D%7B6%7D+)
пожалуйста с решением кто даст с решением поставлю отметку лучший ответ
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
домножаем на 18
2(x + 2) - 18 = 2x + 1 - 3x
2x + 4 - 18 = -x + 1
2x + x = 1 - 4 + 18
3x = 15
x = 15:3
x = 5
Автор ответа:
1
Ответ:
Пошаговое объяснение:
Общий знаменатель 18.
2(х+2)-18=2х+1-3х
2х+4-18=2х+1-3х
3х=1-4+18
3х=15
х=15/3
х=5
Похожие вопросы
Предмет: Русский язык,
автор: Otlichnica475
Предмет: Русский язык,
автор: Жека040896
Предмет: Русский язык,
автор: виииииииииииииииииии
Предмет: Физика,
автор: levinanastya2002